The Effect of Using the Project-Based Learning Model on Critical Thinking Skills in History Learning for Class XI at SMA Negeri 1 Alalak - Anisa Pitriani; Heri Susanto; Dewicca Fatma Nadilla (STKIP Taman Siswa Bima, 2025)
Critical thinking skills are crucial for students in history learning. However, high school teachers often use conventional learning methods that make students less active in history learning. Therefore, innovative and interactive learning models are needed to help improve their critical thinking skills. This study aims to determine the effect of using the project-based learning model on critical thinking skills in history learning for grade XI students at SMA Negeri 1 Alalak. This study used a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The research sample consisted of two classes: an experimental class using the Project-Based Learning model with 31 students and a control class using the problem-based learning model with 31 students. The research instrument was an essay test that had been tested for validity, reliability, difficulty level, and discriminatory power. Data were analyzed using normality, homogeneity, and t-tests with the help of IBM SPSS 29 software. Based on the results of the data analysis, there was an increase in learning outcomes in both the control and experimental classes, but the experimental class showed a more significant increase. In the control class, the average pretest score of 74.35 increased to 78.55 in the posttest, while in the experimental class the average pretest score of 78.55 increased to 85.48 in the posttest with a difference of 6.93 points. The normality test showed that the data was normally distributed (Sig. > 0.05), the homogeneity test showed that the data variance was homogeneous (Sig. 0.144 > 0.05), and the hypothesis test through the Independent Samples Test produced a p-value of 0.001 < 0.05. Thus, it can be concluded that the use of the Project-Based Learning learning model has a significant effect in improving the critical thinking skills of class XI students of SMA Negeri 1 Alalak.